Can you hear me now? Engendering passion and preparedness perceptions with vocal expressions in crowdfunding pitches - Allison, Thomas H.; Warnick, Benjamin J.; Davis, Blakley C.; Cardon, Melissa S. (Journal of Business Venturing, 2022)
The voice is often the only continuous channel of expression in pitch videos. We isolate the influence of entrepreneurs' vocal expressions on funding by examining how valence (positivity/negativity) and arousal (activation) shape funders' perceptions of passion and preparedness. We show that an entrepreneur's high-arousal vocal expressions, whether positive or negative, increase perceptions of their passion. Entrepreneurs are perceived as more prepared when the valence and arousal of their vocal expressions are congruent. We test our hypotheses in the context of rewards-based crowdfunding, using both an experiment and a speech affect analysis of real-world crowdfunding pitches.